Glial Cells and Their Contribution to the Mechanisms of Action of Cannabidiol in Neuropsychiatric Disorders - Scarante, Franciele F.; Ribeiro, Melissa A.; Almeida-Santos, Ana F.; Guimarães, Francisco S.; Campos, Alline C. (Frontiers in Pharmacology, 2021)
Cannabidiol (CBD) is a phytocannabinoid with a broad-range of therapeutic potential in several conditions, including neurological (epilepsy, neurodegenerative diseases, traumatic and ischemic brain injuries) and psychiatric disorders (schizophrenia, addiction, major depressive disorder, and anxiety). The mechanisms responsible for these effects are still unclear, and more than 60 potential molecular targets have been described. Regarding neuropsychiatric disorders, most studies investigating these mechanisms have focused on neuronal cells. Glial cells (astrocytes, oligodendrocytes, microglia), however, also play a crucial role in keeping the homeostasis of the central nervous system. Changes in glial functions have been associated with neuropathological conditions, including those for which CBD is proposed to be useful. Mostly in vitro studies have indicated that CBD modulate the activation of proinflammatory pathways, energy metabolism, calcium homeostasis, and the proliferative rate of glial cells. Likewise, some of the molecular targets proposed for CBD actions are f expressed in glial cells, including pharmacological receptors such as CB1, CB2, PPAR-𝞬, and 5-HT1A. In the present review, we discuss the currently available evidence suggesting that part of CBD effects are mediated by interference with glial cell function. We also propose additional studies that need to be performed to unveil the contribution of glial cells to CBD effects in neuropsychiatric disorders.